Molecular Docking and Pharmacoinformatics Study of Bioactive Compounds in Sweet Flag (Acorus calamus L.) as Antidiabetic Agents Targeting α-Glucosidase - Nasution, Rani Sakila; Dewata, Indang; Yuhelman, Nofri; Sandrawati, Neny; Kusnanda, Arif Juliari (Jurnal Pijar Mipa, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder whose prevalence continues to rise, necessitating safer and more effective therapeutic alternatives. This study aims to explore the potential of active compounds from the calamus plant (Acorus calamus L.) as candidates for α-glucosidase enzyme inhibitors using an in silico approach. Pharmacokinetic screening, toxicity prediction, and Lipinski's Rule of Five screening were conducted to assess the pharmacological suitability of the compounds, followed by molecular docking using MOE 2022 software. The results of the study showed that several compounds from the jeringau plant (Acorus calamus L.), such as galgravin and veraguensin, have strong binding affinity to the α-glucosidase enzyme with docking scores of −8.40 kcal/mol and −8.37 kcal/mol, respectively. Pharmacokinetic prediction results indicate that the test compounds have good absorption and meet druglikeness criteria. This study suggests that active compounds from jeringau have potential for development as natural-based antidiabetic agents. However, this research is limited to computational analysis without experimental data support, and compound selection is based on GC-MS results without further isolation or characterization. Further studies through in vitro and in vivo testing, as well as molecular dynamics simulations and ADMET predictions, are required to validate these findings comprehensively.